Developmental Toxicity of (4S)-2- (4-hydroxy-3-methoxyphenyl) thiazolidine-4-carboxylic acid in Zebrafish ( Danio rerio ) - Akbulut,Cansu (2017)
ABSTRACT (4S)-2-(4-hydroxy-3-methoxyphenyl)thiazolidine-4-carboxylic acid is new synthesized substance obtained from cysteine and valine. Thiazolidine derivates have important biological responses so scientists work intensively on these compounds in recent years. It is obvious that thiazolidine contained compounds will be used in future in the pharmaceutical industry to treat important diseases. Median lethal concentrations (LC50) for 48 h and 96 h were found as 1.106±0.052 mM and 0.804mM ± 0.102 respectively. According to LC50, exposure doses were determined as control, 0.4 mM, 0.2 mM and 0.1 mM (4S)-2-(4-hydroxy-3-methoxyphenyl)thiazolidine-4-carboxylic acid. Developmental toxicity and apoptotic features on zebrafish development were evaluated in this study. The results of this study indicate that (4S)-2-(4-hydroxy-3-methoxyphenyl)thiazolidine-4-carboxylic acid exposure cause developmental defects like pericardial edema, bent spine, tail malformation, blood accumulation, yolk sac edema but on the other hand concentration-dependent decrease in apoptotic rate. Likewise, concentration-dependent decrease in hatching and increase in mortality of embryos were also detected.